Ecopedagogic Based on Video Learning - Durrotun Nafisah; Ety Youhanita; Nur Fithria Wiji Astutik (CV ODIS, 2022)
The COVID-19 pandemic has indirectly forced teachers to adapt to the learning process. The learning process during the COVID-19 pandemic requires teachers to change their way of thinking, how to interact and how to learn in the world of education in digital form. One of the digital forms that will be used in delivering social studies subjects in class VIII in semester 1 is the development of learning videos with sub-materials of changes in space and interactions between areas due to natural factors. The result of learning videos uses the ADDIE development model, which consists of five stages. Each stage of development will produce data used as an evaluation tool for developing learning video media. Finally, the story of learning videos must go through the validation stage so that the videos can be declared eligible for use in the learning process. The results of the validity of media experts on the development of learning videos get a percentage of 93%, with a very suitable category for use. In comparison, the reality of the material experts on the development of learning videos gets a percentage of 95% with a very suitable category for use. And for the validity of the individual trials, the obtained is 83% with a proper type for help, the percentage obtained for small group trials is 88% with a suitable category for use, and for large group trials, the obtained is 96% with a very feasible type. Therefore, based on the validation results that have been carried out, it can be concluded that the video-based eco-pedagogy developed is an innovation ready to be applied to the learning process in the new normal era.